Guidelines for quality control of the Black Sea. Microphytobenthos / Nevrova E.L., Snigireva A.A., Petrov A.N., Kovaleva G.V. / Ed. A.V. Gaevskaya. – Sevastopol; Simferopol: N. Orianda, 2015. – 176 p. (Альгология, 2016)
A guideline for quality control of the marine microphytobenthos consists of methodical recommendations for sampling, treatment, laboratory processing and different kinds of analysis of the Black Sea benthic microalgae.